Monatomic nanofiber catalytic membrane with gradient distribution of catalyst as well as preparation method and application of monatomic nanofiber catalytic membrane
By achieving catalyst gradient distribution in single-atom nanofiber catalytic film, the problem of low reactive oxygen and catalyst utilization caused by uniform distribution of traditional catalysts within the film is solved, and the effect of efficient generation of singlet oxygen and efficient treatment of high-salt high-concentration organic pollutant wastewater is achieved.
Patent Information
- Application Number
- CN202411821934.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-11
AI Technical Summary
The prior art is difficult to efficiently generate singlet oxygen, and the uniform distribution of traditional catalysts within the membrane leads to low utilization of reactive oxygen and catalysts, making it difficult to effectively treat high-salt and high-concentration organic pollutant wastewater.
A single-atom nanofiber catalytic film is used to load a single-atom catalyst on the surface and inside of the membrane fiber through blending-electrospinning method to achieve the gradient distribution of the catalyst and improve the utilization rate of reactive oxygen and catalyst.
It has achieved efficient generation of singlet oxygen, significantly improved the utilization rate of catalysts and reactive oxygen species, and can efficiently treat high-salt and high-concentration organic pollutant wastewater, reaching a mineralization rate of more than 60%.
Smart Images

Figure CN119608245A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a single-atom nanofiber catalytic membrane for generating singlet oxygen, and in particular to a nanofiber catalytic membrane with a high-activity metal-C3N4 single-atom catalyst gradient distribution, a preparation method thereof, and application thereof in degrading high-salt and high-concentration organic pollutant wastewater, belonging to the technical field of membrane separation-catalysis coupling and sewage treatment. Background Art
[0002] Advanced oxidation technology is widely used in wastewater treatment due to its high mineralization efficiency for organic pollutants. For example, advanced oxidation processes such as ozone oxidation, Fenton / Fenton-like reaction, UV and electrochemical oxidation can produce reactive oxygen species, which can then degrade refractory organic matter. Commonly used heterogeneous catalytic ozone oxidation and Fenton reaction convert toxic pollutants into less toxic molecules or short-chain compounds by generating hydroxyl radicals (·OH). However, inorganic ions (such as Cl - 、HCO3 - 、NO3 - ) and natural organic matter (NOM) will quench ·OH, resulting in a decrease in the decomposition rate of pollutants; in contrast, non-free radicals such as singlet oxygen ( 1 O2) is a molecular oxygen in an excited paramagnetic state. It has strong oxidizing properties and is resistant to anion interference. Therefore, it is particularly suitable for catalytic oxidation reactions in high-salt and high-concentration organic environments. How to achieve advanced oxidation processes? 1 The specific generation of O2 is the key to the efficient treatment of high-salinity wastewater.
[0003] At present, studies have reported that materials such as transition metal oxides and carbon-based metal catalysts derived from metal-organic frameworks (MOFs) catalyze the activation of potassium peroxymonosulfate (PMS) to generate 1 O2, but its catalytic activity and selectivity are inhibited due to the inevitable aggregation of active sites. Single-atom catalysts have atomically dispersed metal active sites, unique electronic structures, and maximized atomic utilization. They exhibit excellent oxidation activation ability and high selectivity in catalytic reactions, and are an ideal catalyst for activating PMS and selectively generating 1 Highly efficient catalyst for O2. In the traditional intermittent advanced oxidation process, the catalyst powder is suspended in the solution, and the catalyst nanoparticles are easy to agglomerate, resulting in a low exposure rate of catalytic active sites; the nanoparticles are difficult to recycle, resulting in the loss of catalysts; active oxygen and pollutants rely on diffusion mass transfer, and due to the limited diffusion distance of active oxygen, most pollutants in the bulk solution cannot contact active oxygen, resulting in low active oxygen utilization and pollutant degradation rate. Anchoring nanocatalytic particles on porous or large particle carriers is an effective way to improve their dispersibility, stability and recyclability.
[0004] Membrane catalysis is a new type of membrane process that combines membrane separation process with catalytic process. The catalytic membrane has micrometer and nanometer-scale pores, which can load nanocatalysts into confined channels, constrain catalytic active sites, oxidants, and pollutants in confined spaces, shorten the distance for oxidants and pollutants to diffuse to the active surface, and maximize the contact of reactants; at the same time, the catalytic interface in the pores adsorbs reactants to produce concentration polarization, so that the active oxygen generated at the interface and the pollutants collide effectively, so the pollutant degradation efficiency of the catalytic membrane is much higher than that of the catalyst powder. In particular, the coupling of nanofiber membranes and catalysts solves the problem of poor permeability of traditional nanocatalytic membranes. A Chinese patent (CN117299206A) discloses a simple method for preparing an iron oxide / polyetherimide nanofiber catalytic membrane, in which a polyetherimide nanofiber membrane is prepared by electrospinning, and then the membrane is immersed in a catalyst precursor solution, and iron oxide grows in situ on the fiber surface. The catalytic membrane activates hydrogen peroxide to generate free radicals for efficient degradation of pollutants, but this restricts the effective treatment of high-salt wastewater; at the same time, the catalyst of the catalytic membrane is evenly distributed inside the membrane, resulting in a high active oxygen concentration at the rear end of the pores with low pollutant concentrations, and the utilization rate of the catalyst and active oxygen decreases. How to prepare activated PMS generation 1 The single-atom nanofiber catalytic membrane of O2 and the realization of gradient distribution of catalyst to improve the utilization rate of active oxygen and catalyst are still unresolved technical problems. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention provides a single-atom nanofiber catalytic membrane with a catalyst gradient distribution, a preparation method and an application thereof. The single-atom catalyst inside the nanofiber catalytic membrane of the present invention is distributed in a mass fraction gradient, has a high catalytic active site utilization rate, and generates highly active singlet oxygen in a high proportion, and is particularly suitable for the treatment of high-salt and high-concentration wastewater.
[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows.
[0007] The first aspect of the present invention provides a single-atom nanofiber catalytic membrane with a catalyst gradient distribution, comprising a nanofiber base membrane, and a metal-C3N4 single-atom catalyst gradiently distributed on the surface of the nanofiber base membrane.
[0008] Preferably, the nanofiber base membrane has a thickness of 100 to 300 microns, an average pore size of 0.1 to 1.0 microns, and is made of one of polyacrylonitrile, polyvinylidene fluoride, and polyether sulfone.
[0009] Preferably, the particle size of the metal-C3N4 single atom catalyst is not greater than 1 micron; more preferably, the particle size of the metal-C3N4 single atom catalyst is 40 to 400 nanometers.
[0010] Preferably, the content of the metal-C3N4 single atom catalyst in the single atom nanofiber catalytic membrane is 1wt% to 10wt%; more preferably, the mass ratio of the metal-C3N4 single atom catalyst in the single atom nanofiber catalytic membrane is 3wt% to 6wt%.
[0011] Preferably, the single-atom nanofiber catalytic membrane activates potassium peroxymonosulfate to produce singlet oxygen, and the produced singlet oxygen accounts for 70-100 mol% of the total active oxygen.
[0012] The second aspect of the present invention provides a method for preparing a single-atom nanofiber catalytic membrane with a catalyst gradient distribution, comprising the following steps:
[0013] S1. Prepare precursor A solution, precursor B solution and precursor C solution respectively;
[0014] The precursor A solution is an aqueous solution containing a metal salt and an acid; the precursor B solution is an aqueous solution containing cyanuric acid and / or ammonium sulfate; the precursor C solution is an aqueous solution containing melamine and / or urea;
[0015] S2, mixing the precursor A solution obtained in step S1 with the precursor B solution to obtain a precursor D solution;
[0016] S3, mixing the precursor D solution obtained in step S2 with the precursor C solution obtained in step S1 to obtain a complex solution E, and then filtering to obtain a complex;
[0017] S4, drying and grinding the complex obtained in step S3, and then calcining at 400-600° C. to obtain a metal-C3N4 single atom catalyst;
[0018] S5, adding the dried polymer particles, the metal-C3N4 single atom catalyst obtained in step S4 and the pore-forming agent into a solvent, heating and stirring, so that the metal-C3N4 single atom catalyst is evenly dispersed, and the mass fraction of the metal-C3N4 single atom catalyst is adjusted to obtain spinning solutions with different concentrations of the metal-C3N4 single atom catalyst;
[0019] S6, placing the spinning solution obtained in step S5 in an electrospinning machine for spinning, during which the spinning solutions with different single-atom catalyst concentrations are replaced to obtain a nanofiber catalytic membrane with a gradient distribution of the single-atom catalyst mass fraction;
[0020] S7, immersing the nanofiber catalytic membrane obtained in step S6 in a solution to form pores, and then drying it to obtain a single-atom nanofiber catalytic membrane with a catalyst gradient distribution.
[0021] Preferably, in step S1, the metal salt is at least one of cobalt salt, iron salt, nickel salt and manganese salt; and the acid is at least one of oxalic acid and citric acid.
[0022] Preferably, in step S1, in the A solution, the concentration of the metal salt is 1-10 mmol / L, and the concentration of the acid is 10-35 mmol / L; the concentration of the B solution is 10-40 mmol / L; and the concentration of the C solution is 10-90 mmol / L;
[0023] More preferably, in the A solution, the concentration of the metal salt is 2-10 mmol / L, and the concentration of the acid is 10-30 mmol / L; the concentration of the B solution is 10-20 mmol / L; and the concentration of the C solution is 10-30 mmol / L.
[0024] Preferably, in step S2, the mixing and stirring time is 0.5 to 2 hours.
[0025] Preferably, in step S3, the mixing and stirring time is 4 to 8 hours; and the filtering method is suction filtration.
[0026] Preferably, the process of step S4 is: placing the complex in a vacuum oven at 60-80°C for drying overnight, then grinding it to obtain a powdered complex, then placing the powdered complex in a tubular furnace, heating it to 400-600°C at a rate of 2-5°C / min in an inert gas atmosphere, keeping it warm for 4-6h, and then naturally cooling it to room temperature to obtain a metal-C3N4 single atom catalyst.
[0027] Preferably, in step S5, the polymer is one of polyacrylonitrile, polyvinylidene fluoride, and polyether sulfone;
[0028] The pore-forming agent is one of polyvinyl pyrrolidone and polyethylene glycol;
[0029] The solvent is one of N-methylpyrrolidone, dimethyl pyrrolidone, and acetone;
[0030] In the spinning solution, the mass percentages of the dried polymer particles, the pore-forming agent and the metal-C3N4 single-atom catalyst obtained in step S4 are 6-18wt%, 2-12wt% and 1-10wt% respectively;
[0031] The heating and stirring temperature is 60-80° C., and the stirring time is 6-12 hours.
[0032] Preferably, the process of step S6 is: take a spinning solution with a metal-C3N4 single-atom catalyst concentration of 7wt% to 10wt% and spin for 3 to 6 hours, replace the spinning solution with a metal-C3N4 single-atom catalyst concentration of 4wt% to 6wt% and continue spinning for 3 to 6 hours, replace the spinning solution with a metal-C3N4 single-atom catalyst concentration of 1wt% to 3wt% and continue spinning for 3 to 6 hours, to obtain a nanofiber catalytic membrane with a gradient distribution of the mass fraction of the single-atom catalyst;
[0033] The spinning conditions are: environmental humidity 25-65% RH, spinning distance 5-20 cm, spinning voltage 5-25 kV, and feed speed 0.1-0.5 mm / min.
[0034] Preferably, the process of step S7 is: immersing the nanofiber catalytic membrane in deionized water, ultrasonicating in a water bath for 0.5 to 1.5 hours, and placing it at 50°C to 70°C for 24 to 48 hours to wash away the pore-forming agent, followed by drying to obtain a single-atom nanofiber catalytic membrane with a catalyst gradient distribution.
[0035] The third aspect of the present invention provides the use of the above-mentioned single-atom nanofiber catalytic membrane with a catalyst gradient distribution in wastewater treatment, wherein the single-atom nanofiber catalytic membrane with a catalyst gradient distribution activates peroxymonosulfate to generate singlet oxygen, thereby oxidatively degrading pollutants in the wastewater.
[0036] Preferably, the conditions for the single-atom nanofiber catalytic membrane with a catalyst gradient distribution to oxidize and degrade pollutants in wastewater are: reaction temperature 20-40°C, reaction pH 2-10, salt content 0-20000 ppm, and peroxymonosulfate addition amount 0.5-4 mM;
[0037] More preferably, the salt content is 5000-20000 ppm.
[0038] Preferably, the pollutant is at least one of antibiotics, endocrine disruptors and dyes.
[0039] More preferably, the antibiotic is at least one of tetracycline, sulfonylmoxazole, and penicillin, the endocrine infection agent is at least one of bisphenol A, phthalates, and alkylphenols, and the dye is at least one of methylene blue, rhodamine B, orange G, and galactocyanine.
[0040] Compared with the prior art, the present invention has the following advantages:
[0041] 1) The present invention loads and intersperses single-atom catalysts on the surface and inside of membrane fibers through the method of blending-electrospinning, which improves the stability of single-atom catalyst loading in the membrane compared to existing process technologies such as suction filtration membrane formation and impregnation-calcination; at the same time, the single-atom nanofiber catalytic membrane has a criss-crossed fiber structure with high porosity and good pore connectivity, which improves the membrane permeability of the catalytic membrane.
[0042] 2) The present invention realizes the gradient distribution of single-atom catalysts inside the nanofiber membrane, thereby realizing the gradient distribution of active oxygen concentration in the membrane pores, so that it matches the gradually decreasing pollutant concentration in the pores. Compared with the current catalytic membrane in which the catalyst is evenly distributed inside the membrane, the utilization rate of the catalyst and active oxygen is greatly improved, and the amount of catalyst added is reduced while ensuring excellent catalytic degradation effect.
[0043] 3) The present invention greatly improves the catalytic degradation efficiency of organic pollutants by nanofiber membranes, and can achieve instant filtration and catalytic degradation of small organic molecules in sewage; the membrane efficiently activates peroxymonosulfate and selectively generates singlet oxygen, and can achieve a mineralization rate of more than 60% for high-salt and high-concentration refining wastewater; at the same time, the membrane has good reusability, providing a new and effective method for wastewater treatment. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] In order to more clearly illustrate the technical solutions in the specific implementation modes of the present invention, the drawings required for use in the specific implementation modes will be briefly introduced below. Obviously, the drawings described below are only some specific implementation modes of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0045] Figure 1 It is a schematic diagram of preparing a nanofiber catalytic membrane with a gradient distribution of mass fraction of single atom catalyst in step S6 of the preparation method of the present invention.
[0046] Figure 2 The single-atom nanofiber catalytic membrane prepared in Example 1 of the present invention activates PMS to produce singlet oxygen 1 O2 detection result diagram. DETAILED DESCRIPTION
[0047] In order to further understand the present invention, preferred embodiments of the present invention are described below. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.
[0048] The single-atom nanofiber catalytic membrane with a catalyst gradient distribution of the present invention comprises a nanofiber base membrane and a metal-C3N4 single-atom catalyst gradiently distributed on the surface of the nanofiber base membrane.
[0049] In the present invention, the thickness of the nanofiber-based membrane is preferably 100 to 300 microns, the average pore size is 0.1 to 1.0 microns, and the material includes but is not limited to polyacrylonitrile, polyvinylidene fluoride, and polyether sulfone. The particle size of the metal-C3N4 single-atom catalyst is not greater than 1 micron. The content of the metal-C3N4 single-atom catalyst in the single-atom nanofiber catalytic membrane with a catalyst gradient distribution is 1 to 10wt%. It can be understood that the metal-C3N4 single-atom catalyst is mixed into the spinning solution for spinning, and the smaller catalyst particle size is easily buried in the membrane matrix, thereby affecting the exposure rate of the catalytic active sites; and the larger catalyst particle size has a greater impact on the porosity and stability of the single-atom nanofiber catalytic membrane. At the same time, it can be understood that if the catalyst loading is less, the single-cycle catalytic degradation efficiency of the single-atom nanofiber catalytic membrane will be reduced; and more catalyst loading will have a greater impact on the pore size and porosity of the single-atom nanofiber catalytic membrane, resulting in a decrease in membrane permeability. Based on comprehensive test verification and membrane system operation cost estimation, the present invention preferably has a particle size of 40 to 400 nanometers for the metal-C3N4 single atom catalyst, and preferably has a content of 3wt% to 6wt% for the metal-C3N4 single atom catalyst in the single atom nanofiber catalytic membrane.
[0050] In the present invention, it is preferred that the single-atom nanofiber catalytic membrane activates potassium persulfate to produce singlet oxygen, and the produced singlet oxygen accounts for 70 to 100 mol% of the total active oxygen.
[0051] The method for preparing the single-atom nanofiber catalytic membrane with a catalyst gradient distribution of the present invention comprises the following steps:
[0052] S1. Prepare precursor A solution, precursor B solution and precursor C solution respectively;
[0053] The precursor A solution is an aqueous solution composed of a metal salt such as cobalt, iron, nickel, manganese, an acid such as oxalic acid, citric acid, etc., and water in any ratio; in the A solution, the concentration of the metal salt is 1-10 mmol / L, and the concentration of the acid is 10-35 mmol / L; the precursor B solution is an aqueous solution composed of a monomer such as cyanuric acid, ammonium sulfate, etc. and water in any ratio; the concentration of the B solution is 10-40 mmol / L; the precursor C solution is an aqueous solution composed of a monomer such as melamine, urea, etc. and water in any ratio; the concentration of the C solution is 10-90 mmol / L;
[0054] S2, mixing the precursor A solution obtained in step S1 with the precursor B solution and stirring for 0.5 to 2 hours to obtain a precursor D solution;
[0055] S3, mixing the precursor D solution obtained in step S2 with the precursor C solution obtained in step S1 and stirring for 4 to 8 hours to obtain a complex solution E, and then filtering to obtain a complex;
[0056] S4, placing the complex obtained in step S3 in a vacuum oven at 60-80°C for drying overnight, and then grinding to obtain a powdery complex, then placing the powdery complex in a tube furnace, heating to 400-600°C at a rate of 2-5°C / min in an inert atmosphere (such as nitrogen), keeping the temperature for 4-6h, and then naturally cooling to room temperature to obtain a metal-C3N4 single atom catalyst;
[0057] S5, adding the dried polymer particles, the metal-C3N4 single atom catalyst obtained in step S4 and the pore-forming agent into a solvent, heating and stirring at 60° C. to 80° C. for 6 to 12 hours to uniformly disperse the metal-C3N4 single atom catalyst, and adjusting the mass fraction of the metal-C3N4 single atom catalyst to obtain spinning solutions with different concentrations of the metal-C3N4 single atom catalyst;
[0058] The polymer is one of polyacrylonitrile, polyvinylidene fluoride, polyether sulfone, etc., the pore-forming agent is one of polyvinyl pyrrolidone, polyethylene glycol, etc., the solvent is one of N-methylpyrrolidone, dimethylamide, acetone, etc., and the contents of the polymer, pore-forming agent, and metal-C3N4 single-atom catalyst in the spinning solution are 6wt% to 18wt%, 2wt% to 12wt%, and 1wt% to 10wt%, respectively;
[0059] S6, take a spinning solution with a metal-C3N4 single-atom catalyst concentration of 7wt% to 10wt% and spin for 3 to 6h, replace the spinning solution with a metal-C3N4 single-atom catalyst concentration of 4wt% to 6wt% and continue spinning for 3 to 6h, replace the spinning solution with a metal-C3N4 single-atom catalyst concentration of 1wt% to 3wt% and continue spinning for 3 to 6h, and finally obtain a nanofiber catalytic membrane with a gradient distribution of the mass fraction of the single-atom catalyst; the process parameters of the spinning process are: ambient humidity 25 to 65% RH, spinning distance 5 to 20cm, spinning voltage 5 to 25kV, feed speed 0.1 to 0.5mm / min;
[0060] S7. Immerse the nanofiber catalytic membrane with a gradient distribution of the mass fraction of the single-atom catalyst obtained in step S6 in deionized water, perform water bath ultrasound for 0.5 to 1.5 hours, and place it at 50°C to 70°C for 24 to 48 hours to wash away the pore-forming agent, and then dry it to obtain a single-atom nanofiber catalytic membrane with a gradient distribution of the catalyst.
[0061] The single-atom nanofiber catalytic membrane with a catalyst gradient distribution of the present invention can be used in wastewater treatment. Under certain temperature, pH and salt content, the single-atom nanofiber catalytic membrane with a catalyst gradient distribution activates peroxymonosulfate to generate active oxygen mainly in the singlet state, and oxidatively degrades pollutants in the wastewater.
[0062] In the present invention, the pollutant may be at least one of an antibiotic, an endocrine disruptor, and a dye. The antibiotic is at least one of tetracycline, sulfonylmoxazole, and penicillin, the endocrine disruptor is at least one of bisphenol A, phthalates, and alkylphenols, and the dye is at least one of methylene blue, rhodamine B, orange G, and Ganguohong.
[0063] In the present invention, the conditions for the oxidation degradation of pollutants in wastewater by the single-atom nanofiber catalytic membrane with a preferred catalyst gradient distribution are: reaction temperature of 20-40°C, reaction pH of 2-10, salt content of 5000-20000ppm, and peroxymonosulfate addition of 0.5-4mM. After testing, the single-atom nanofiber catalytic membrane with a catalyst gradient distribution can achieve a pollutant mineralization rate of more than 60% for the degradation of high-salt refining wastewater with a salt content greater than 5000ppm. It can be understood that in the treatment of wastewater in a low-salt or salt-free environment, the single-atom nanofiber catalytic membrane with a catalyst gradient distribution of the present invention has the same catalytic degradation performance.
[0064] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention will be further described in detail below in conjunction with embodiments.
[0065] In the following examples, various processes and methods not described in detail are conventional methods known in the art. Unless otherwise specified, the materials, reagents, devices, instruments, equipment, etc. used in the following examples can be obtained from commercial sources.
[0066] Example 1
[0067] S1. Add 0.15 g of ferric nitrate nonahydrate and 0.15 g of oxalic acid to 100 g of water to obtain a precursor A solution; add 0.6 g of cyanuric acid to 125 g of water to obtain a precursor B solution; add 0.8 g of melamine to 160 g of water to obtain a precursor C solution;
[0068] S2, mixing the precursor A solution obtained in step S1 with the precursor B solution and stirring for 0.5h to obtain a precursor D solution;
[0069] S3, mixing the precursor D solution obtained in step S2 with the precursor C solution obtained in step S1 and stirring for 4 hours to obtain a complex solution E, and then filtering to obtain a complex;
[0070] S4, placing the complex obtained in step S3 in a vacuum oven at 60°C for drying overnight, and then grinding to obtain a powdery complex, then placing the powdery complex in a tube furnace, heating to 600°C at a rate of 4°C / min in an inert gas environment, keeping the temperature for 4 hours, and then naturally cooling to room temperature to obtain a Fe-C3N4 single atom catalyst;
[0071] S5. Add dried polyacrylonitrile particles, polyvinyl pyrrolidone, and Fe-C3N4 single-atom catalyst to N-methylpyrrolidone, heat and stir at 60°C to 80°C for 12 hours to obtain a spinning solution. Prepare three spinning solutions containing different concentrations of Fe-C3N4 single-atom catalyst, whose contents of polyacrylonitrile (wt%): polyvinyl pyrrolidone (wt%): Fe-C3N4 single-atom catalyst (wt%) are: 12wt%: 6wt%: 8wt%, 12wt%: 6wt%: 5wt%, 12wt%: 6wt%: 2wt%, respectively, and are recorded as spinning solution 1, spinning solution 2, and spinning solution 3, respectively.
[0072] S6, such as Figure 1 As shown, take spinning solution 1 and load it into the syringe, use a 22-gauge single nozzle needle, and spin for 4 hours; then replace the spinning solution in the syringe with spinning solution 2, and continue spinning for 4 hours; finally, replace the spinning solution in the syringe with spinning solution 3, and spin for 4 hours, and finally obtain a nanofiber catalytic membrane with a gradient distribution of the mass fraction of the single atom catalyst. During the spinning process, the ambient humidity is controlled at 30% RH, the spinning distance is 10 cm, the spinning voltage is 10 kV, and the feed speed is 0.15 mm / min.
[0073] S7. Immerse the nanofiber catalytic membrane obtained in step S6 in deionized water, perform water bath ultrasound for 0.5 h, and place it at 60°C for 24 h to wash away the pore-forming agent, and then dry it to obtain a single-atom nanofiber catalytic membrane with a catalyst gradient distribution, which is recorded as Fe-C3N4 single-atom nanofiber catalytic membrane.
[0074] The Fe-C3N4 single-atom nanofiber catalytic membrane prepared in Example 1 was used to activate PMS, and the detection results were tested. Figure 2 It can be seen that the presence of the characteristic triplet peak of singlet oxygen tested by paramagnetic resonance indicates that the Fe-C3N4 single atom nanofiber catalytic membrane activates PMS to generate singlet oxygen, which is beneficial to the oxidation and degradation of organic small molecules by the Fe-C3N4 single atom nanofiber catalytic membrane in a high salt environment.
[0075] The performance of the Fe-C3N4 single-atom nanofiber catalytic membrane prepared in Example 1 was tested. The catalytic membrane was used to catalyze the degradation of a single pollutant solution. Tetracycline was selected as the pollutant, and the pollutant concentration was 30 ppm. NaCl was added to the solution to - The content reached 10000ppm, the amount of permonosulfate added was 1mM, the initial pH was adjusted to 7, the reaction temperature was 25°C, and the pollutant solution could achieve a tetracycline removal rate of 98% and a mineralization rate of 65% after a single membrane pass.
[0076] Example 2
[0077] S1. Add 0.025 g of cobalt acetate tetrahydrate and 0.6 g of citric acid to 100 g of water to obtain a precursor A solution; add 0.6 g of ammonium sulfate to 125 g of water to obtain a precursor B solution; add 0.8 g of urea to 160 g of water to obtain a precursor C solution;
[0078] S2, mixing the precursor A solution obtained in step S1 with the precursor B solution and stirring for 0.5h to obtain a precursor D solution;
[0079] S3, mixing the precursor D solution obtained in step S2 with the precursor C solution obtained in step S1 and stirring for 4 hours to obtain a complex solution E, and then filtering to obtain a complex;
[0080] S4, placing the complex obtained in step S3 in a vacuum oven at 60°C for drying overnight, and then grinding to obtain a powdery complex, then placing the powdery complex in a tubular furnace, heating to 550°C at a rate of 2°C / min in an inert gas environment, keeping the temperature for 4 hours, and then naturally cooling to room temperature to obtain a Co-C3N4 single atom catalyst;
[0081] S5. Add dried polyvinylidene fluoride particles, polyethylene glycol, and Co-C3N4 single-atom catalyst to N-methylpyrrolidone, heat and stir at 60°C to 80°C for 12 hours to obtain a spinning solution. Prepare three spinning solutions containing different concentrations of Co-C3N4 single-atom catalyst, whose contents of polyvinylidene fluoride (wt%): polyethylene glycol (wt%): Co-C3N4 single-atom catalyst (wt%) are: 9wt%: 9wt%: 8wt%, 9wt%: 9wt%: 5wt%, 9wt%: 9wt%: 2wt%, respectively, and are recorded as spinning solution 1, spinning solution 2, and spinning solution 3, respectively.
[0082] S6, take spinning solution 1 and put it into a syringe, use a 22-gauge single nozzle needle, and spin for 4 hours (spinning stage 1); then replace the spinning solution in the syringe with spinning solution 2, and continue spinning for 4 hours (spinning stage 2); finally replace the spinning solution in the syringe with spinning solution 3, and spin for 4 hours (spinning stage 3), and finally obtain a nanofiber catalytic membrane with a gradient distribution of the mass fraction of the single atom catalyst. During the spinning process, the ambient humidity is controlled at 30% RH, the spinning distance is 10 cm, the spinning voltage is 10 kV, and the feed speed is 0.15 mm / min.
[0083] S7. Immerse the nanofiber catalytic membrane obtained in step S6 in deionized water, perform water bath ultrasound for 0.5 h, and place it at 60°C for 24 h to wash away the pore-forming agent, and then dry it to obtain a single-atom nanofiber catalytic membrane with a catalyst gradient distribution, which is recorded as Co-C3N4 single-atom nanofiber catalytic membrane.
[0084] The performance of the Co-C3N4 single-atom nanofiber catalytic membrane prepared in Example 2 was tested. The catalytic membrane was used to catalytically degrade high-salt refinery wastewater, the salinity of the wastewater was about 20000ppm, the COD content was about 1000ppm, the amount of permonosulfate added was 4mM, the initial pH was adjusted to 7, the reaction temperature was 25°C, and the pollutant solution could achieve a COD removal rate of 62% after passing through the membrane twice.
[0085] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0086] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.
Claims
1. A single-atom nanofiber catalytic membrane with a catalyst gradient distribution, characterized in that: It includes a nanofiber-based membrane and a metal-C3N4 single-atom catalyst gradiently distributed on the surface of the nanofiber-based membrane.
2. The single-atom nanofiber catalyst membrane with a catalyst gradient distribution according to claim 1, characterized in that: The nanofiber base membrane has a thickness of 100 to 300 microns and an average pore size of 0.1 to 1.0 microns; And / or, the material of the nanofiber-based membrane includes one of polyacrylonitrile, polyvinylidene fluoride and polyether sulfone; and / or, the particle size of the metal-C3N4 single atom catalyst is not greater than 1 micron; and / or, the metal includes one of cobalt, iron, nickel and manganese; And / or, the content of the metal-C3N4 single atom catalyst in the single atom nanofiber catalytic membrane is 1wt% to 10wt%.
3. The single-atom nanofiber catalytic membrane with a catalyst gradient distribution according to claim 2, characterized in that: The particle size of the metal-C3N4 single atom catalyst is 40 to 400 nanometers; And / or, the content of the metal-C3N4 single atom catalyst in the single atom nanofiber catalytic membrane is 3wt% to 6wt%.
4. The single-atom nanofiber catalytic membrane with a catalyst gradient distribution according to claim 1, characterized in that: The single-atom nanofiber catalytic membrane activates potassium peroxymonosulfate to generate singlet oxygen, and the generated singlet oxygen accounts for 70-100 mol% of the total active oxygen.
5. The method for preparing a single-atom nanofiber catalytic membrane with a catalyst gradient distribution according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Prepare precursor A solution, precursor B solution and precursor C solution respectively; The precursor A solution is an aqueous solution containing a metal salt and an acid; the precursor B solution is an aqueous solution containing cyanuric acid and / or ammonium sulfate; the precursor C solution is an aqueous solution containing melamine and / or urea; S2, mixing the precursor A solution obtained in step S1 with the precursor B solution to obtain a precursor D solution; S3, mixing the precursor D solution obtained in step S2 with the precursor C solution obtained in step S1 to obtain a complex solution E, and then filtering to obtain a complex; S4, drying and grinding the complex obtained in step S3, and then calcining at 400-600° C. to obtain a metal-C3N4 single atom catalyst; S5, adding the dried polymer particles, the metal-C3N4 single atom catalyst obtained in step S4 and the pore-forming agent into a solvent, heating and stirring, so that the metal-C3N4 single atom catalyst is evenly dispersed, and the mass fraction of the metal-C3N4 single atom catalyst is adjusted to obtain spinning solutions with different concentrations of the metal-C3N4 single atom catalyst; S6, placing the spinning solution obtained in step S5 in an electrospinning machine for spinning, during which the spinning solutions with different single-atom catalyst concentrations are replaced to obtain a nanofiber catalytic membrane with a gradient distribution of the single-atom catalyst mass fraction; S7, immersing the nanofiber catalytic membrane obtained in step S6 in a solution to form pores, and then drying it to obtain a single-atom nanofiber catalytic membrane with a catalyst gradient distribution.
6. The method for preparing a single-atom nanofiber catalytic membrane with a catalyst gradient distribution according to claim 5, characterized in that: In step S1, the metal salt is at least one of cobalt salt, iron salt, nickel salt and manganese salt; the acid is at least one of oxalic acid and citric acid; In the A solution, the concentration of the metal salt is 1-10 mmol / L, and the concentration of the acid is 10-35 mmol / L; the concentration of the B solution is 10-40 mmol / L; the concentration of the C solution is 10-90 mmol / L; And / or, in step S2, the mixing and stirring time is 0.5 to 2 hours; And / or, in step S3, the mixing and stirring time is 4 to 8 hours, and the filtering method is suction filtration; And / or, the process of step S4 is: placing the complex in a vacuum oven at 60-80°C for drying overnight, subsequently grinding to obtain a powdered complex, then placing the powdered complex in a tubular furnace, heating to 400-600°C at a rate of 2-5°C / min in an inert gas atmosphere, keeping the temperature for 4-6 hours, and then naturally cooling to room temperature to obtain a metal-C3N4 single atom catalyst; And / or, in step S5, the polymer is one of polyacrylonitrile, polyvinylidene fluoride, and polyether sulfone; The pore-forming agent is one of polyvinyl pyrrolidone and polyethylene glycol; The solvent is one of N-methylpyrrolidone, dimethyl pyrrolidone, and acetone; In the spinning solution, the mass percentages of the dried polymer particles, the pore-forming agent and the metal-C3N4 single-atom catalyst obtained in step S4 are 6-18wt%, 2-12wt% and 1-10wt% respectively; The heating and stirring temperature is 60 to 80°C, and the stirring time is 6 to 12 hours; And / or, the process of step S6 is: take a spinning solution with a metal-C3N4 single-atom catalyst concentration of 7wt% to 10wt% and spin for 3 to 6 hours, replace the spinning solution with a metal-C3N4 single-atom catalyst concentration of 4wt% to 6wt% and continue spinning for 3 to 6 hours, replace the spinning solution with a metal-C3N4 single-atom catalyst concentration of 1wt% to 3wt% and continue spinning for 3 to 6 hours, to obtain a nanofiber catalytic membrane with a gradient distribution of the mass fraction of the single-atom catalyst; The spinning conditions are: ambient humidity 25-65% RH, spinning distance 5-20 cm, spinning voltage 5-25 kV, feed speed 0.1-0.5 mm / min; And / or, the process of step S7 is: immersing the nanofiber catalytic membrane in deionized water, ultrasonicating in a water bath for 0.5 to 1.5 hours, and placing it at 50°C to 70°C for 24 to 48 hours to wash away the pore-forming agent, and then drying to obtain a single-atom nanofiber catalytic membrane with a catalyst gradient distribution.
7. Use of the single-atom nanofiber catalytic membrane with a catalyst gradient distribution according to any one of claims 1 to 4 in wastewater treatment, characterized in that: The single-atom nanofiber catalytic membrane with a catalyst gradient distribution activates peroxymonosulfate to generate singlet oxygen, thereby oxidizing and degrading pollutants in wastewater.
8. The use of the single-atom nanofiber catalytic membrane with a catalyst gradient distribution in wastewater treatment according to claim 7, characterized in that: The conditions for the single-atom nanofiber catalytic membrane with a catalyst gradient distribution to oxidize and degrade pollutants in wastewater are: reaction temperature 20-40° C., reaction pH 2-10, salt content 0-20000 ppm, and peroxymonosulfate addition amount 0.5-4 mM; And / or, the pollutant is at least one of antibiotics, endocrine disruptors, and dyes.
9. The use of the single-atom nanofiber catalytic membrane with a catalyst gradient distribution in wastewater treatment according to claim 8, characterized in that: The salt content is 5000-20000 ppm.
10. The use of the single-atom nanofiber catalytic membrane with a catalyst gradient distribution in wastewater treatment according to claim 8, characterized in that: The antibiotic is at least one of tetracycline, sulfonylmoxazole, and penicillin; the endocrine infection agent is at least one of bisphenol A, phthalates, and alkylphenols; and the dye is at least one of methylene blue, rhodamine B, orange G, and red.
Citation Information
Patent Citations
Photocatalyst fibers and method for producing same
CN102821851A
Preparation method of tail gas purifying catalyst with gradient-distributed active components
CN104492434A
Preparation method of continuous cellulose-nanometal composite aerogel fibers
CN106111195A
Cobalt-nickel alloy / carbon composite electrocatalyst with gradient distribution and preparation method and application thereof
CN111910290A
Monatomic catalyst for activating persulfate to generate pure singlet oxygen as well as preparation method and application thereof
CN113058635A
Cited By
Catalyst for realizing efficient mineralization of perfluorinated pollutants by utilizing solar photo-thermal conversion as well as preparation method and application of catalyst
CN122321965A